2021
DOI: 10.1038/s41398-021-01207-y
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of childhood maltreatment and DNA methylation: candidate gene and epigenome-wide approaches

Abstract: Childhood maltreatment is a major risk factor for chronic and severe mental and physical health problems across the lifespan. Increasing evidence supports the hypothesis that maltreatment is associated with epigenetic changes that may subsequently serve as mechanisms of disease. The current review uses a systematic approach to identify and summarize the literature related to childhood maltreatment and alterations in DNA methylation in humans. A total of 100 empirical articles were identified in our systematic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
102
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(109 citation statements)
references
References 188 publications
5
102
2
Order By: Relevance
“…The specific contributors to NR3C1 hypermethylation in our study participants remain unknown. Although previous studies have provided support for the hypothesis that NR3C1 hypermethylation in children can result from environmental adversities, such as early life stress [ 54 ], we were not able to address this possibility since our utilized cohort did not include information on early life adversities. Moreover, we cannot exclude the possibility that genetic variations can also influence NR3C1 methylation levels, similar to findings from other stress-responsive genes such as the FK506 binding protein 5 ( FKBP5 ) gene [ 55 , 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…The specific contributors to NR3C1 hypermethylation in our study participants remain unknown. Although previous studies have provided support for the hypothesis that NR3C1 hypermethylation in children can result from environmental adversities, such as early life stress [ 54 ], we were not able to address this possibility since our utilized cohort did not include information on early life adversities. Moreover, we cannot exclude the possibility that genetic variations can also influence NR3C1 methylation levels, similar to findings from other stress-responsive genes such as the FK506 binding protein 5 ( FKBP5 ) gene [ 55 , 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…to be more susceptible to childhood maltreatment-related impairments in maternal behaviours. 126 Childhood maltreatment has been shown to increase DNA methylation and to modulate the expression of various genes 127 including the oxytocin receptor gene. DNA methylation of the oxytocin receptor gene has been shown to be linked to social behaviour, emotional behaviour and psychiatric diseases.…”
Section: Effects Of Adverse Environments In Early-life Stages On the Oxytocin System In Humansmentioning
confidence: 99%
“…FKBP5 is a gene known to regulate the glucocorticoid receptor, an important part of the hypothalamic pituitary adrenal (HPA) axis that binds cortisol—an adrenal stress hormone that also regulates metabolism—and thus a good candidate to mediate an epigenetic response to social stress. Many studies have identified associations between adverse childhood experiences, socioeconomic adversity, and other environmental stressors with lower DNA methylation of FKBP5 across various tissues as reviewed in Parade et al ( 33 ). Demethylation of intron 2 of FKBP5 has been shown to disrupt the HPA axis and contribute to glucocorticoid resistance, higher cortisol levels, and prolonged recovery following exposure to stress ( 34 ).…”
Section: Introductionmentioning
confidence: 99%